1971
DOI: 10.1152/ajplegacy.1971.221.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Blood gases in hibernating and active ground squirrels: HbO2 affinity at 6 and 38 C

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Pa O 2 values of Ͻ80 mmHg have been reported in euthermic animals of other heterothermic species (5,15,29,40), although such low Pa O 2 levels have not been observed consistently (16,56). Low Pa O 2 , high Pa CO 2 , and low pH have been observed regularly in euthermic AGS in our laboratory over the past several years.…”
Section: Discussionmentioning
confidence: 49%
“…Pa O 2 values of Ͻ80 mmHg have been reported in euthermic animals of other heterothermic species (5,15,29,40), although such low Pa O 2 levels have not been observed consistently (16,56). Low Pa O 2 , high Pa CO 2 , and low pH have been observed regularly in euthermic AGS in our laboratory over the past several years.…”
Section: Discussionmentioning
confidence: 49%
“…There may be an accumulation of carbon dioxide in body fluids during entrance into torpor at very low ambient temperatures, as was described for dormice (Kreienbühl et al, 1976;Elvert and Heldmaier, 2000b). Blood analyses have shown that when the temperature of the blood decreased, its pH increased and P CO ∑ decreased (Musacchia and Volkert, 1971;Kreienbühl et al, 1976;Rodeau and Malan, 1979;Malan, 1982). To maintain a constant P CO ∑ and pH, additional storage of large quantities of CO 2 are required (Malan, 1982).…”
Section: Preparation For Entrance Into Torpormentioning
confidence: 88%
“…In addition to the hypoxic challenges associated with life underground and life at high altitude, many sciurid rodents face additional gas transport challenges associated with depressed ventilation and episodic breathing during winter hibernation (Milsom, 1992;Milsom and Jackson, 2011;Webb and Milsom, 1994). In hibernating ground squirrels, prolonged periods of apnea can result in wide fluctuations in arterial P O2 and plasma pH (Maginniss and Milsom, 1994;Malan et al, 1973;Musacchia and Volkert, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors that modulate Hb-O 2 affinity are Cl -ions (Chiancone et al, 1972) and temperature (Antonini and Brunori, 1971), as well as protons and CO 2 , which also bind preferentially to deoxy-Hb and promote O 2 unloading in the tissue capillaries via the Bohr effect (Perutz, 1983;Weber and Fago, 2004). Increases in blood-O 2 affinity during winter hibernation have been documented in a number of mammals, and such changes are generally attributable to reductions in red cell DPG, increases in pH and/or decreased body temperature (Burlington and Whitten, 1971;Maginniss and Milsom, 1994;Musacchia and Volkert, 1971;Revsbech et al, 2013;Tempel and Musacchia, 1975 hibernation, experiments on purified Hbs are required to evaluate the independent and joint effects of DPG, pH and temperature on Hb-O 2 affinity under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%